Pemasaran Jasa Pendidikan - Idham Amirulloh; Devika Hidayahtus S.; Rafi Ilham R; Ummi Mardiyah (FKIP, Universitas Palangka Raya, 2024)
In this day and age, educational institutions must compete in order to meet or exceed the wants and needs of the community as consumers or customers who use their educational services. Of course this is related to the marketing carried out by these institutions and schools. This is where the school needs to pay attention to managing its marketing strategy, because it determines the number of students enrolled in the school. In the world of education, how to manage effective communication and trusting relationships, covering aspects ranging from the programs offered to the stages of the tutoring process related to infrastructure and human resources. The results of educators and alumni who can influence students as customers and the wider community. Therefore, to compete with other educational institutions, you need to manage your educational marketing strategy as well as possible. The concept of marketing strategy includes: (1) market segmentation/classification, (2) market positioning, (3) market entry strategy, (4) marketing mix strategy, (5) timing strategy or the right time. The marketing strategy of an educational institution certainly requires careful planning, including a SWOT analysis (strengths, weaknesses, opportunities and threats), to minimize errors and obstacles in the marketing process.